Supply Chain Performance of SMEs: The Role of Triple-A Strategy - Baziedy Aditya Darmawan; Rif'atul Laili Maulida; Mochamad Nasito (KINERJA, 2021)
Agility, adaptability, and alignment (henceforth referred as triple-A) are supply chain strategy that supports sustainable competitive advantage. The previous studies found that triple-A is a principle to achieve the superior supply chain performance. However, a study that investigate the triple-A of SME, especially in culinary industry is still limited. This study aims to investigate the effect of triple-A towards SME supply chain performance in culinary industry. Using convenience sampling technique, 98 SMEs were involved in this study. The results of the multiple regression analysis show that the triple-A supply chain strategy has a significant effect on supply chain performance. This finding explain that SME supply chain performance are affected by their ability in managing supply chain strategy that categorized as agility, adaptability, and alignment. This finding give an empirically supports that agility, adaptability, and alignment are antecedent variables of SME supply chain performance.Keywords: Triple-A, agility, adaptability, alignment, supply chain, performance.